Autophagy in glaucoma pathogenesis: Therapeutic potential and future perspectives - Li, Min; Gao, Zhao-Lin; Zhang, Quan-Peng; Luo, Ai-Xiang; Xu, Wei-Ye; Duan, Tian-Qi; Wen, Xu-Peng; Zhang, Ru-Qi; Zeng, Ru; Huang, Ju-Fang (Frontiers in Cell and Developmental Biology, 2022)
Glaucoma is a common blinding eye disease characterized by progressive loss of retinal ganglion cells (RGCs) and their axon numbers, progressive loss of visual field, and optic nerve atrophy. Autophagy plays a pivotal role in the pathophysiology of glaucoma and is closely related to the pathogenesis of glaucoma. Targeting autophagy and blocking the apoptosis of RGCs provides emerging guidance for the treatment of glaucoma. In this paper, we provide a systematic review of the mechanisms, and targets of interventions related to autophagy in glaucoma, and discuss the outlook of emerging ideas, techniques, and multidisciplinary combinations, to provide a new basis for further research and prevention of glaucomatous visual impairment.